2022
DOI: 10.30762/jeels.v4i1.49
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence Quotient (IQ) as a Predictor of Reading Comprehension and Writing Achievement of EFL Learners

Abstract: This study aimed at investigating Intelligent Quotient (IQ) as a predictor of reading comprehension and writing achievement as well as to correlate the students' reading comprehension with their writing achievement. The participant of the study were 32 senior high school Indonesian students. There are three instruments used in this study, those are IQ test, reading comprehension test, and writing test. Upon obtaining the whole data needed, Pearson Product Moment formula was employed to determine the correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The significant impact of intelligence on reading comprehension (t = 5.43, p < .05) and listening ability (t = 5.55, p < .05) supports prior works (Esmaeel and Zahra, 2015;Ningrum and Wibowo, 2017). This finding suggests that the brain network of people with higher intelligence has shorter path lengths and thus better cognitive ability (Langer et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The significant impact of intelligence on reading comprehension (t = 5.43, p < .05) and listening ability (t = 5.55, p < .05) supports prior works (Esmaeel and Zahra, 2015;Ningrum and Wibowo, 2017). This finding suggests that the brain network of people with higher intelligence has shorter path lengths and thus better cognitive ability (Langer et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…Empirically, there is no doubt that intelligence is good predictors of language skills. A study conducted with a group of 32 secondary Indonesian school students revealed a significant contribution of intelligence to reading comprehension (Ningrum and Wibowo, 2017). However, Corso et al (2016) found no direct link between intelligence (measured using Raven's Progressive Matrices), and reading comprehension among fourth and sixth graders in Brazil.…”
Section: Introductionmentioning
confidence: 98%